Ploidy variation of Musa hybrids from crosses - Oselebe, H.O.; Tenkouano, A.; Pillay, M. (2006)
Plantain and banana (Musa spp) breeding involves crossing 3x (triploid) landraces to 2x (diploid) accessions as female and male parents, respectively, selecting 4x (tetraploid) and 2x primary hybrids from the 3x - 2x progenies, and crossing 4x - 2x hybrids to produce secondary 3x hybrids. In these crosses, complex ploidy and genome arrays occur frequently making it difficult to predict the products of crosses. The objective of the study was (a) to determine the ploidy of progenies of 2x – 2x, 2x – 4x and 4x – 2x crosses, and (b) to assess the agronomic characteristics of diploid and triploid progenies recovered from the same or similar crosses. The breeding population involved progenies of interploidy crosses field established in a randomized complete block design (RCBD) with three eplications. Ploidy was determined using Flow cytometry analysis of nuclear DNA content and chloroplast characteristics. Results indicated that progenies of 2x–2x crosses were predominantly diploid (99.7%), those of 2x–4x crosses were mainly diploid (96.2%), while the 4x–2x crosses produced predominantly triploid progenies (94.1%). Very highly significant differences (P<0.001) among and within ploidy groups were observed for mean number of chloroplasts and the most frequent number of chloroplasts in stomatal guard cells of progenies. Diploid hybrids recovered from crosses had shorter days to flowering, plant height and bunch weight compared to triploid hybrids.